2005
DOI: 10.1103/physrevlett.94.214501
|View full text |Cite
|
Sign up to set email alerts
|

Thermal Patterning of a Critical Polymer Blend

Abstract: Utilizing the Soret effect, we have employed a moderately focused laser beam (30 microm, 20 mW) to write spatial composition patterns into layers of the critical polymer blend poly(dimethyl siloxane)/poly(ethyl-methyl siloxane) (PDMS/PEMS, M(w)=16.4/22.8 kg/mol) both in the one- and in the two-phase region a few degrees above and below the critical temperature T(c)=37.7 degrees C. Because of the critical divergence of the Soret coefficient, moderate temperature gradients are sufficient to induce composition mo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
36
2

Year Published

2006
2006
2022
2022

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 48 publications
(39 citation statements)
references
References 21 publications
1
36
2
Order By: Relevance
“…4b). These findings contradict several theoretical studies claiming that D T should be independent of particle size (16)(17)(18)(19)(20)26), based on ambiguous experimental results from thermal field flow fractionation (4) that were probably biased by nonlinear thermodiffusion in large thermal gradients (15).…”
Section: Theoretical Approachcontrasting
confidence: 83%
See 2 more Smart Citations
“…4b). These findings contradict several theoretical studies claiming that D T should be independent of particle size (16)(17)(18)(19)(20)26), based on ambiguous experimental results from thermal field flow fractionation (4) that were probably biased by nonlinear thermodiffusion in large thermal gradients (15).…”
Section: Theoretical Approachcontrasting
confidence: 83%
“…The Soret coefficient is defined as ratio S T ϭ D T /D, which determines the magnitude of thermodiffusion in the steady state. Although the above exponential distribution could motivate an approach based on Boltzmann equilibrium statistics, it is commonly argued that thermodiffusion without exception is a local nonequilibrium effect that requires fluid dynamics, force fields, or particle-solvent potentials (16)(17)(18)(19)(20). However, in a previous paper (15), we demonstrated that for moderate temperature gradients the thermal fluctuations of the particle are the basis for a local equilibrium.…”
Section: Theoretical Approachmentioning
confidence: 78%
See 1 more Smart Citation
“…Thermophoresis has the potential to analyze the particle-solvent interaction of nanoscaled particles and biomolecules. Moreover, it is a versatile tool to manipulate or concentrate molecule concentrations in solution [12,13]. In addition to biotechnological applications, a natural thermophoretic setting is found in pores of rock near hot springs on the floor of the ocean, possibly involved in molecular evolution [14,15].…”
mentioning
confidence: 99%
“…The Soret effect is thus also referred to as the thermal diffusion effect. This effect was discovered independently by Ludig in Vienna in 1856 and by Soret in Geneva in 1879, and it has been studied mostly in oxide [1], electrolyte [2] and polymer [3] solutions.…”
Section: Introductionmentioning
confidence: 90%